Traces of Latin Education in the Old Norse World - Ommundsen, Åslaug (Intellectual Culture in Medieval Scandinavia, c. 1100-1350, ed. Stefka Georgieva Eriksen, 2016)
Traces of Latin Education in the Old Norse World